Efek Moderasi Orientasi Strategi antara Karakteristik Kewirausahaan terhadap Keberhasilan Usaha Pariwisata - Fenri Abraham Stevi Tupamahu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
TTourism has become one of the leading sectors in the Indonesian national economy and has become an important sector in contributing to the country's foreign exchange. This study aims to 1) identify and test the effect of entrepreneurial characteristics on the success of tourism businesses in coastal areas and small islands, 2) determine the role of strategic orientation moderation between the influence of entrepreneurial characteristics on the success of tourism businesses. This type of research is explanatory research (explanatory research) with survey methods, quantitative analysis approaches. The sample of this research is tourism business in coastal areas and small islands in Ambon City, Central Maluku Regency and Southeast Maluku Regency, Maluku Province, amounting to 40 units. Sampling using a purposive sampling technique. The criteria used in sampling are businesses that have been operating for at least five years and are individually owned businesses. Data analysis uses the statistical method of Moderated Regression Analysis. The results of this study prove that, the better the entrepreneurial characteristics that are indicated in terms of innovation, leadership, ways of making decisions, attitudes and responsibilities towards change, work effectively, efficiently, vision of the future and attitudes towards risk affect the increase in the success of tourism businesses in coastal areas and small islands in Maluku. Strategic orientation as moderation has a significant positive effect between the characteristics of entrepreneurship and the success of coastal tourism businesses and small islands in Maluku. Keywords: Entrepreneurship Characteristics, Strategic Orientation, Business Success.